An Analysis of the Problem Students use the PISA Assessment Guidelines for Junior Schools - Hasriani Ishak; YL. Sukestiyarno; Rochmad Rochmad; Wardono Wardono; Scolastika Mariani (Universitas Negeri Semarang, 2021)
Analysis of student problems in solving PISA questions is important in increasing the PISA level. This article describes the students problems for junior high school students in solving PISA questions. This research was conducted in junior high schools in the city of Ternate by taking a random sample of 50 junior high school students. then analyzed 20 students at different schools by taking students who like mathematics. We analyzed the student problems in terms of students' learning habits in class based on the PISA assessment guidelines for each level. and offers a recommendation for learning that can increase junior high school students' PISA levels.